WAZHĀĪFU AL-USRAH `ALĀ T`ALLUMI AL-`ARABIYYAH LI ṬOLABATI AL-MADRASAH AL-ṠANĀWIYAH AL-ISLĀMIYYAH AL-HUKŪMIYYAH BI BERAU - Irawan, Yolandha Paramitha; Maulana, Muhammad Rifqi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Family is the most important figure in education. Even though students are assigned to schools, families have an influence on student learning outcomes directly or indirectly. Some of the families of students at MAN Berau, East Kalimantan, think that the responsibility for educating is delegated to the teacher, including learning Arabic. This type of research is field research(field research), a qualitative approach with the case study method, data sources were collected through observation, interviews and documentation. The subjects of this study were families of junior high school alumni, students and Arabic language teachers at MAN Berau. The object of this research is the role of the family towards general junior high school alumni students in learning Arabic. The results of the study show that there are 3 family roles for 10th grade junior high school alumni in learning Arabic at this school, namely: 1) providing learning facilities in the form of dictionaries and the internet, 2) guiding students in student learning, 3) providing motivation and advice. There are 3 obstacles, namely: 1) the family has never learned Arabic, 2) Arabic is not yet considered a main subject, 3) the family does not know where to take Arabic lessons. The impact consists of Positive Impact and Negative Impact. The positive impacts are 1) growing students' enthusiasm in learning Arabic, 2) students are faster in doing assignments, 3) students' knowledge of Arabic is constantly growing. As for the negative impact that is caused, the teaching responsibility is completely focused on the teacher.